Implementation of Legal Certainty Values ​​in the Process of Increasing Land Rights in Demak Regency - Nugroho, Prastyo Adi (Jurnal Konstatering, 2024)
Background of the study is In the context of improving land status in Indonesia, the implementation of legal certainty is an important issue that needs serious attention. Demak Regency as one of the regions in Indonesia also faces challenges in terms of improving land status which requires clear legal certainty. Land rights issues, land conflicts, and investment and development are the main focus in this context. Improving land status from Building Use Rights to Ownership Rights or other status changes requires a structured and transparent legal process. In this case, a study of the implementation of legal certainty related to improving land status in Demak Regency can provide a clear picture of the challenges, obstacles, and solutions that can be implemented to increase the effectiveness of the legal system in this case. The research method used by the author in this study is Empirical Research with a qualitative approach, using primary data and secondary data, data collection methods are carried out by interviews and observations, from the data collected will be analyzed using descriptive methods. The results of the study are the Regulation of the Minister of ATR/BPN Number 1339 of 2022 as the latest legal basis that strengthens the process of improving the status of Building Use Rights (HGB) to Ownership Rights (HM) in Demak Regency. This regulation complements regulations such as UUPA No. 5 of 1960, PP No. 24 of 1997, Regulation of the Minister of State for Agrarian Affairs/Head of BPN No. 3 of 1997, PP No. 46 of 2002, and Circular Letter of the Head of BPN-600-1900 dated July 31, 2003, and provide convenience for the community in the process of improving land status. The case of Mr. Budi and Mrs. Siti is a real example of the successful implementation of this regulation, although there were several obstacles such as completeness of files and understanding of procedures. The efforts of BPN Demak in socialization, improving services, and handling special cases also contributed to the smooth running of this process. Overall, this regulation provides legal certainty, benefits, and justice for the community in realizing stronger land ownership.